Non-Exonuclease Domain POLE Mutations Associated with Immunotherapy Benefit. (28th February 2022) - Dong, Sharlene; Zakaria, Heba; Hsiehchen, David
Abstract: Inactivating mutations in the exonuclease domain of POLE induce somatic hypermutation resulting in a high tumor mutation burden (TMB) and are associated with immune checkpoint inhibitor (ICI) benefit. POLE mutations outside the exonuclease domain predicted to be deleterious are also observed in cancers, but it is unknown whether they are similarly associated with response to ICIs. We present a patient with hepatocellular carcinoma with a rare POLE mutation (V1368M) outside the exonuclease-domain predicted to be deleterious, a low TMB (1 mut/Mb), and microsatellite stability, who demonstrated an exceptional response to pembrolizumab. To support the generalizability of this finding, an analysis of 1278 patients with advanced cancers harboring low or intermediate TMB treated with ICIs showed that missense non-exonuclease domain POLE mutations were associated with greater overall survival. In contrast, among patients with advanced cancers without ICI exposure, POLE mutations were not associated with overall survival. These results demonstrate that a subset of missense POLE mutations may represent predictive biomarkers independent of TMB. Pathogenic POLE mutations outside the exonuclease domain may result in altered functions beyond DNA replication and proofreading which render cancers sensitive to ICIs. Abstract : This article presents the case of a patient with hepatocellular carcinoma with a rare POLE mutation outside the exonuclease domain, who demonstrated an exceptional response to pembrolizumab.